EFEKTIVITAS BAHAN AJAR MOBILE E-LEARNING INTERAKTIF DALAM PEMBELAJARAN FISIKA SISWA KELAS XI SMAN 10 PADANG - Nora Sofiana (PILLAR OF PHYSICS EDUCATION, 2014)
Development physics lectures based on mobile e-learning is one solution to effective learning process. The purpose of this research is to determine the validity, practicality, and effectivity of mobile e-leaning interactive lectures. The type of research is Research and Development. Design in this research is experiment before and after. The object of research is mobile e-learning interactive lectures. Instruments collecting data are sheet of validaty, sheet of practicality, and cognitive aspects of student learning outcomes. Techniques of data analysis used for validity product, and practicality use likert scale. Effectivity analysis used t test. Based on analysis data there are three results. Firstly, validity of learning materials with average value is 84.7. Second, the average value of learning materials practicality of mobile e-learning interactive by teachers and students is 87.39. Third, learning materials mobile e-learning interactive is effective to increase student learning outcomes with average value of pretest and posttest is 56.59 and 85.76 respectively. Thus, it can be concluded that the learning lectures of mobile e-learning interactive is proper and effective to improve student learning outcomes